2005
DOI: 10.1203/01.pdr.0000175641.39056.7a
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Angiogenic Factors in Placentas with Chorioamnionitis after Preterm Birth

Abstract: Chorioamnionitis and funisitis are associated with neonatal morbidity and mortality. We hypothesized that chorioamnionitis may stress fetal endothelium, activate proinflammatory gene transcription. and affect angiogenic homeostasis in fetal capillaries. Placentas from preterm infants were stained for heat-shock protein 70, nuclear factor-B, hypoxia-inducible factor-1␣, and vascular endothelial growth factor (VEGF). VEGF receptors (VEGF-R) 1 and 2 as well as the receptor tyrosine kinase with immunoglobulin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 56 publications
0
32
1
2
Order By: Relevance
“…21 Intrauterine exposure to proinflammatory cytokines or antenatal infection may prime the fetal lung such that minimally injurious postnatal events provoke an uncontrolled pulmonary inflammatory status that affects normal alveolarization and pulmonary vascular development. 22,23 Moreover, we found that although the lungs matured during fetal inflammation, ELBW infants with RDS in the presence of chorioamnionitis were susceptible to postnatal injurious events.…”
Section: Discussionmentioning
confidence: 80%
“…21 Intrauterine exposure to proinflammatory cytokines or antenatal infection may prime the fetal lung such that minimally injurious postnatal events provoke an uncontrolled pulmonary inflammatory status that affects normal alveolarization and pulmonary vascular development. 22,23 Moreover, we found that although the lungs matured during fetal inflammation, ELBW infants with RDS in the presence of chorioamnionitis were susceptible to postnatal injurious events.…”
Section: Discussionmentioning
confidence: 80%
“…33 Inhibition of microvascular development was striking in the lungs of infants with BPD 34 and placentas with chorioamnionitis. 35 Parallel responses occured in the fetal sheep lungs. Chemokines associated with inflammation and angiostasis were expressed by inflammatory cells and bronchioles.…”
Section: Lung Injury Following Chorioamnionitismentioning
confidence: 99%
“…Funisitis, characterized by neutrophilic infiltration, associated with upregulation of vascular adhesion molecules in the vessels of the umbilical cord (16) and activation of endothelial inflammatory processes in the placental capillaries (17), reflects the most invasive form of prenatal inflammation with a systemic response of the fetus, that has been associated with higher neonatal mortality (18) and BPD (19).…”
mentioning
confidence: 99%